EVOLUÇÃO DO USO DA TERRA MICROBACIA DO CÓRREGO DO AÇUDE, EM JATAÍ- GO - DOI 10.5216/bgg.v22i2.15385 - Scopel, Iraci; T. Katzer, Rosália; R. Silva, Márcio; A. de Melo, Nágela; M. Peixinho, Dimas (Boletim Goiano de Geografia, 2011)
.